Research on Consumer Initial Trust Model Based on Internet of Things. Issue 1 (January 2021) - Wang, Ai-Ling; Li, Lei-ming; Xu, Guo-ling
Abstract: With the rapid development of the Internet, consumers are getting more and more diversified information and information channels. Information channel and information content play a vital role in the initial trust of consumers. On the basis of receiving a certain amount of information and information valence, consumers are influenced by information channels to generate corresponding perceived value, thus generating and establishing initial trust. When the information channel is the customer side, the interaction between information quantity and information valence has the strongest regulating effect on perceived value. When the information channel is an enterprise, information quantity and information interaction have the weakest regulating effect on perceived value.